Anti-PD-1 antibody enhances homeostatic proliferation–induced antitumor immunity during lymphopenia recovery - Yang, Zike; Zhu, Ying; Wang, Qian; Lin, Qing; Liu, Yahui (Frontiers in Immunology, 2025)
IntroductionLymphopenia induced by radiotherapy or chemotherapy can promote homeostatic proliferation of residual or adoptive lymphocytes, potentially enhancing antitumor immunity. However, this immunity diminishes rapidly with tumor progression, and the underlying mechanisms remain unclear. This study investigates the role of PD-1 signaling in homeostatic proliferation–induced antitumor immunity in malignant melanoma.MethodsWe evaluated T-cell dynamics in lymphopenic mice, analyzing PD-1 expression, IFN-γ production by CD8+ T cells, and T-cell cytotoxicity during homeostatic proliferation. The PD-1/PD-L1 axis was blocked using anti-PD-1 antibodies to assess its impact on T-cell function, dendritic cell (DC) activation, and memory T-cell differentiation.ResultsAlthough T cells proliferated continuously in lymphopenic mice, IFN-γ+ CD8+ T cells declined over time. PD-1 expression on T cells increased progressively and correlated negatively with effector T-cell cytotoxicity. PD-1 blockade enhanced the recognition of tumor-associated antigens (TAAs) by homeostatically proliferating (HP) T cells, activated DCs, and increased IFN-γ+ CD8+ T-cell numbers. Additionally, it boosted T-cell cytotoxicity and promoted the conversion of tumor-specific effector T cells into central memory T cells.DiscussionThese findings indicate that the PD-1/PD-L1 axis plays a critical role in immune tolerance during homeostatic proliferation. Anti-PD-1 therapy may enhance antitumor immunity during lymphopenia recovery after chemotherapy or radiotherapy, offering a potential strategy to sustain T-cell–mediated tumor control.